Graham/Hijmans/Kamp/Watkins Family Reunion at Lake Nacimiento - Watkins, Howard::::::::: (1989)
Group photo: Front: Greg Graham holding Stanley Graham; Back: Carey Hijmans, Jackie Hijmans, Christine Watkins, Robin Watkins, Marty Hijmans holding Jamie Hijmans, Jesse Graham, Peter Graham, Frances Kamp, Adam Watkins, Jerry Kamp Richard Graham, Gail Graham and ? Robin Watkins facing camera and holding white Frisbee